A scoping review of psychiatric conditions associated with chronic pain in the homeless and marginally housed population - Rintoul, Kathryn; Song, Esther; McLellan-Carich, Rachel; Schjelderup, Elizabeth N. R.; Barr, Alasdair M. (Frontiers in Pain Research, 2023)
The present review sought to examine and summarise the unique experience of concurrent pain and psychiatric conditions, that is often neglected, within the population of homeless individuals. Furthermore, the review examined factors that work to aggravate pain and those that have been shown to improve pain management. Electronic databases (MEDLINE, EMBASE, psycINFO, and Web of Science) and the grey literature (Google Scholar) were searched. Two reviewers independently screened and assessed all literature. The PHO MetaQAT was used to appraise quality of all studies included. Fifty-seven studies were included in this scoping review, with most of the research being based in the United States of America. Several interacting factors were found to exacerbate reported pain, as well as severely affect other crucial aspects of life that correlate directly with health, within the homeless population. Notable factors included drug use as a coping mechanism for pain, as well as opioid use preceding pain; financial issues; transportation problems; stigma; and various psychiatric disorders, such as post-traumatic stress disorder, depression, and anxiety. Important pain management strategies included cannabis use, Accelerated Resolution Therapy for treating trauma, and acupuncture. The homeless population experiences multiple barriers which work to further impact their experience with pain and psychiatric conditions. Psychiatric conditions impact pain experience and can work to intensify already adverse health circumstances of homeless individuals.